2020
DOI: 10.3390/ijms21176090
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactants Induce Antimicrobial Peptide Production through the Activation of TmSpatzles in Tenebrio molitor

Abstract: Biosurfactant immunomodulatory activities in mammals, nematodes, and plants have been investigated. However, the immune activation property of biosurfactants in insects has not been reported. Therefore, here, we studied the defense response triggered by lipopeptides (fengycin and iturin A), glycolipids (rhamnolipid), and cyclic polypeptides (bacitracin) in the coleopteran insect, mealworm Tenebrio molitor. The in vitro antimicrobial activities against Gram-positive (Staphylococcus aureus) and Gram-negative (Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
(86 reference statements)
1
4
0
Order By: Relevance
“…Although it was expressed in all tissues and the whole body, the highest expression was observed in the intestine, fat bodies, and MTs 24 hours after microbial infection. Furthermore, in agreement with previous studies [ 99 , 100 ], Tm-Spz-like knockdown larvae exposed to E. coli exhibited significantly lower viability. These findings endorsed the downregulation of 11 encoding Gram-negative AMP genes (out of 15 genes tested).…”
Section: T Molitor Gene Expression Studies Related To Microb...supporting
confidence: 92%
See 2 more Smart Citations
“…Although it was expressed in all tissues and the whole body, the highest expression was observed in the intestine, fat bodies, and MTs 24 hours after microbial infection. Furthermore, in agreement with previous studies [ 99 , 100 ], Tm-Spz-like knockdown larvae exposed to E. coli exhibited significantly lower viability. These findings endorsed the downregulation of 11 encoding Gram-negative AMP genes (out of 15 genes tested).…”
Section: T Molitor Gene Expression Studies Related To Microb...supporting
confidence: 92%
“…After that, in 2020 the same authors reported the response of biosurfactants (bacitracin, fengycin, iturin A, and rhamnolipids) in modulating several T.molitor Spätzle, namely Spz3 (Genbank CAH1376064), Spz4 (Genbank MT075617), Spz6 (Genbank CAH1365756), and Spz-like (Genbank MZ708792) along with AMP expression [ 100 ]. In larvae inoculated with biosurfactants, the expression of AMPs through activation of Tm-Spz genes in hemocytes was observed.…”
Section: T Molitor Gene Expression Studies Related To Microb...mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that Spz proteins have promiscuous roles in the innate immunity of insects against pathogens [ 4 ]. Furthermore, Tm Spz proteins can function as central immune modulators for biosurfactant-mediated AMP production in T. molitor [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other established model systems are protozoa such as Acanthamoeba castellanii , which was used to study Salmonella enterica sv. Typhimurium [ 2 ], the yellow mealworm Tenebrio molitor , which was analyzed in respect to antimicrobial peptide production in several of the submitted manuscripts [ 3 , 4 , 5 ], and larvae of the greater wax moth Galleria mellonella [ 6 ].…”
mentioning
confidence: 99%